Revista de Neuro-psiquiatría: bibliometric analysis and trends during the 2020-2024 period - Pascual-Guevara, Milagros (2024)
Objective: To describe the bibliometric indicators and trends in the scientific production of the Revista de Neuro-Psiquiatría, recently indexed in Scopus. Materials and methods: A search strategy was designed to collect publications registered by Scopus between 2020 and 2024. The variables collected by the SciVal tool were grouped into institutional productivity, author metrics, collaboration patterns, and most cited articles. At the same time, the Bibliometrix package reported collaboration between countries, thematic trends, and the spectrum of reference publications over time. The information was summarily reported in graphs and tables. Results: A total of 187 documents were published, with an average of 1.35 citations per document, and predominance of neurology and mental health topics. The most prolific author, with the highest h-index was Mario Cornejo-Olivas, with a total of 12 documents, whereas Jeff Huarcaya-Victoria had the highest impact, with 4.6 citations per document. Half of the publications came from the Ministry of Health, and the Anglo-American Clinic had the highest impact with 12.2 citations per document. Collaboration mainly involved national authors, but there were also foreign contributors, mostly from the United States and Germany. The analysis of references revealed a higher number of citations from works recently published in the journal. Conclusions: The Revista de Neuro-Psiquiatría, a Peruvian publication with a notable history has followed a relevant trajectory and has been recently indexed in Scopus due to the significance of its publications on neurology and mental health. Strengthening the collaboration networks at national and international levels would allow it an even greater global visibility.